2020
DOI: 10.1136/bmjopen-2020-041386
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and metabolic characteristics of the Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIADEM-I) randomised clinical trial cohort

Abstract: ObjectivesDiabetes Intervention Accentuating Diet and Enhancing Metabolism-I (DIADEM-I) is the first randomised controlled trial (RCT) in the Middle East and North Africa (MENA) region testing the effectiveness of an intensive lifestyle intervention (ILI) for weight loss and diabetes remission. We report on the recruitment process and baseline characteristics of the DIADEM-I cohort based on origin (Middle East vs North Africa), and waist circumference.DesignDIADEM-I is an open-label randomised, controlled, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…A more recent meta-analysis of 28 RCTs showed that lifestyle interventions were more effective than the standard care regarding the glycemic control of subjects with T2DM, particularly when there was weight loss [29]. These results have also been reported in other systematic reviews and meta-analyses all supporting the beneficial effects of lifestyle interventions, regardless of study design, on weight loss and weight maintenance, delay of T2DM onset and progression and decreased risk for CVD [24,27,28,[205][206][207][208][209][210], as well as reduced or eliminated need for anti-diabetic medications [27,127,128,148]. Both shorter-term (6-12 months) and longer-term (>12 months) studies showed that more intensive lifestyle interventions (i.e., medications alone vs medications plus diet plus 5-6 aerobic training sessions/week, duration 30-60 min, of which 2 to 3 sessions were combined aerobic and resistance training) led to greater HbA1c reduction (6.5% compared to 1% with less intensive interventions) [148][149][150] and significant reduction in antidiabetic medications (up to 73% with lifestyle interventions compared to 23% in the control group) [148].…”
Section: Effects Of Intensive Lifestyle (Diet + Exercise + Behavior M...supporting
confidence: 59%
See 1 more Smart Citation
“…A more recent meta-analysis of 28 RCTs showed that lifestyle interventions were more effective than the standard care regarding the glycemic control of subjects with T2DM, particularly when there was weight loss [29]. These results have also been reported in other systematic reviews and meta-analyses all supporting the beneficial effects of lifestyle interventions, regardless of study design, on weight loss and weight maintenance, delay of T2DM onset and progression and decreased risk for CVD [24,27,28,[205][206][207][208][209][210], as well as reduced or eliminated need for anti-diabetic medications [27,127,128,148]. Both shorter-term (6-12 months) and longer-term (>12 months) studies showed that more intensive lifestyle interventions (i.e., medications alone vs medications plus diet plus 5-6 aerobic training sessions/week, duration 30-60 min, of which 2 to 3 sessions were combined aerobic and resistance training) led to greater HbA1c reduction (6.5% compared to 1% with less intensive interventions) [148][149][150] and significant reduction in antidiabetic medications (up to 73% with lifestyle interventions compared to 23% in the control group) [148].…”
Section: Effects Of Intensive Lifestyle (Diet + Exercise + Behavior M...supporting
confidence: 59%
“…The Look AHEAD Trial, the Diabetes Remission Clinical Trial (DiRECT) and the Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIADEM-I) highlighted the potential for T2DM remission, defined as the maintenance of euglycemia (complete remission) or prediabetes level of glycemia (partial remission) with no diabetes medication for at least 1 year, with a weight loss of 15 kg or more within one year following a low or a very low-calorie diet, and also using meal replacements [125][126][127][128] in people undergoing weight loss treatment. In the Look AHEAD trial, when compared with the control group, the intensive lifestyle arm (more visits, 175 min/week unsupervised physical activity, dietary modification counseling, and a weight loss goal of 10%) resulted in at least partial diabetes remission in 12% of participants as compared with 2% in the control group [125].…”
Section: Low Calorie Diets For Weight Lossmentioning
confidence: 99%
“…The DIADEM study demonstrated that the TDR intervention is feasible in Qatar, which may translate to the Kuwaiti population, although North African participants made up a higher proportion than Middle Eastern participants which may indicate the reduced uptake of the intervention in patient population from the Gulf region [ 14 , 44 ]. This study also included an exercise component, which was advocated by the dietitians in the current study as a motivator.…”
Section: Discussionmentioning
confidence: 99%
“…La consecución de los objetivos de las investigaciones estuvo dada principalmente por la remisión de la DM2, la reducción en el peso corporal de 5 al 10%. El estudio DIANEM-I [54] concuerda en que, mientras más anticipada se realice la intervención en los estilos de vida, se pueden alcanzar mejores resultados, la probabilidad de conseguir una remisión de diabetes mediada por la pérdida de peso es más factible mientras el diagnóstico de la enfermedad haya sido reciente y a más temprana edad.…”
Section: Discussionunclassified